Ruptura del letargo en semillas de durazno (Prunus pérsica L.) variedad abridor por acción de frío y ácido giberélico - Acosta Herrera, Franklin Rolando (2012)
The present investigation had per object to determine the rupture of the lethargy in peach seeds (Prunus pérsica L.) variety opener per action of cold and gibberellic acid. The utilized hormone was gibberellic acid and its applied doses they were 100 gibberellic acid ppm, 200 gibberellic acid ppm and 300 gibberellic acid ppm; refrigeration was also used at 50C. The investigative work was carried out in the canton Patate, matrix parish, county of Tungurahua, in the factory of liquors “The Forge.” The laboratory works were carried out under conditions of ambient temperature 190C, 50% of relative humidity, heliophany 1.760 hours of average yearly and 2.119 m.s.n.m. The design experimental employee was a D.C.A. with 4 treatments and 3 repetitions, the taking of data was made during 40 days, to which were carried out the statistical analysis by means of Statistical Analysis System (SAS). The procedure ANOVA was used for the variance analysis and test of Tukey (0,05). He was also carried out an economic analysis of each treatment in study, estimating the cost of production. Of the results he/she settles down that the best treatment is the T3 (300 ppm of Gibberellic acid), because it stimulates the germination of seeds of peach variety opener to the 7,33 days. The treatment T3 (300 ppm of Gibberellic acid) it is the one that presented smaller cost of production with a value of U$D 0,25 and the treatment T4 (Refrigeration at 50C) it presented the biggest value in 0,45 of cost of production. To achieve that the seeds of peach variety opener germinate to the 7,33 days, it is recommended to apply 300 gibberellic acid ppm.